Safety of street vended food and the effectiveness of an intervention to improve hygienic practices among street vendors in the district of Kandy. - Wickrematilake, M.S.K (My University, 2007)
Results of the pre intervention survey showed that the baseline knowledge was poor in the areas of food contamination, food borne diseases, safe handling, personal hygiene, time temperature control and handling high risk cooked foods. Vendors had unfavorable views, particularly towards the available facilities and supportive services available to maintain a conducive environment to provide consumers with safer food. However, positive attitudes regarding personal hygiene were not observed in practices. The vendors had minimal personal hygiene and over 50 percent were seen to handle cooked food with bare hands. It was revealed that over 50 percent of the study population had received information on safe food handling through Public Health Inspectors. Standard method (International Standards Organization) was used for the enumeration of selected microbiological profile. According to the health department criteria, boiled gram, cooked rice packets and string hoppers were of unacceptable. quality. E coli was detected in more than 90 present of samples of boiled gram.